Nonaqueous electrolyte secondary battery

By introducing SOx on the negative electrode of the nonaqueous electrolyte secondary battery to form a low resistance SEI film, the problem of increasing resistance and decreasing capacity after storage of the battery is solved, and excellent storage characteristics are achieved.

CN119905634APending Publication Date: 2025-04-29PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411491672.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-10-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult to reduce the resistance increase rate and ensure a high capacity maintenance rate after storage of the nonaqueous electrolyte secondary battery.

Method used

By forming a suitable cover on the negative electrode, the sulfur (S) element is introduced in the form of SOx, a low resistance SEI film is formed to reduce Li loss, thereby improving the storage characteristics of the battery.

Benefits of technology

It has achieved the suppression of the increase in resistance after storage and the reduction of capacity maintenance rate, and the storage characteristics of the nonaqueous electrolyte secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905634A_ABST
    Figure CN119905634A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte secondary battery (100) is provided with a positive electrode (50), a negative electrode (60), and a non-aqueous electrolyte (80). The negative electrode (60) is provided with a negative electrode active material layer (64) containing a negative electrode active material, and the negative electrode active material is provided with a carbon material and an amorphous carbon coating layer covering the carbon material. The negative electrode active material has an intensity ratio (D / G) of a peak intensity D at 1360 cm <-1 > to a peak intensity G at 1580 cm <-1 > in Raman spectroscopy measured by Raman spectroscopy of 0.3-0.5. The non-aqueous electrolyte solution (80) contains at least a sulfur-based electrolyte salt and a non-aqueous solvent, and the non-aqueous solvent contains a carbonate-based solvent and methyl acetate. Here, the SOx concentration of the negative electrode active material layer (64), which is calculated on the basis of an XPS spectrum measured by X-ray photoelectron spectroscopy, is 0.3 at% or more. According to the technology disclosed herein, it is possible to provide a non-aqueous electrolyte secondary battery having improved storage characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries have been widely used as portable power supplies for personal computers and mobile terminals, as well as power supplies for vehicles such as battery electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).

[0003] In general, a non-aqueous electrolyte secondary battery is composed of an electrode body having a positive electrode and a negative electrode, and a non-aqueous electrolyte housed in a battery case. As related technologies, for example, Patent Documents 1 to 3 can be cited. In Patent Document 1, in order to improve rate characteristics, storage capacity retention rate, and high-temperature storage gas generation, a non-aqueous electrolyte comprising oxalate, a compound having two or more cyclic carboxylic anhydride skeletons in the molecule, and a chain carboxylic acid ester with a carbon number of 5 or less is disclosed. Patent Document 2 discloses a non-aqueous electrolyte comprising an ester solvent and a carbonate solvent but not containing a sulfur compound. In addition, Patent Document 3 discloses a secondary battery having a negative electrode comprising at least a carbon fiber aggregate and lithium metal.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-129682

[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-103240

[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-160730 Summary of the Invention

[0009] After storage, it is difficult for non-aqueous electrolyte secondary batteries to simultaneously reduce the rate of resistance increase (low resistance) and ensure a high capacity retention rate (high capacity retention rate). On the other hand, in recent years, there has been a desire to improve the storage characteristics of non-aqueous electrolyte secondary batteries (for example, to suppress the rate of resistance increase after storage and to suppress the decrease in capacity retention rate).

[0010] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a non-aqueous electrolyte secondary battery having improved storage characteristics.

[0011] The non-aqueous electrolyte secondary battery disclosed herein comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode comprises a negative electrode active material layer containing a negative electrode active material, wherein the negative electrode active material comprises a carbon material and an amorphous carbon coating layer covering the carbon material. The negative electrode active material has a Raman spectrum of 1360 cm-1 as measured by Raman spectroscopy. -1 The peak intensity D and 1580 cm -1 The intensity ratio (D / G) of the peak intensity G is 0.3 to 0.5. The non-aqueous electrolyte solution contains at least a sulfur-based electrolyte salt and a non-aqueous solvent, and the non-aqueous solvent contains a carbonate-based solvent and methyl acetate. Here, the SOx concentration of the negative electrode active material layer is 0.3 atomic % or greater, and the SOx concentration is calculated based on the XPS spectrum measured by X-ray photoelectron spectroscopy.

[0012] In the non-aqueous electrolyte secondary battery constructed as described above, after activation treatment, sulfur (S) is introduced into the film formed on the negative electrode in the form of SOx, thereby forming a suitable film on the negative electrode. This film has low resistance and reduces lithium loss due to irreversible reactions. As a result, a non-aqueous electrolyte secondary battery with excellent storage characteristics (particularly, suppressed resistance increase and suppressed capacity retention rate reduction) is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a cross-sectional view schematically showing the internal structure of a lithium-ion secondary battery according to one embodiment.

[0014] Figure 2 This is an exploded schematic diagram showing the structure of a wound electrode body of a lithium-ion secondary battery according to one embodiment. DETAILED DESCRIPTION

[0015] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that matters not mentioned in this specification and matters required for the implementation of the present invention can be understood as design matters based on the prior art in this field by those skilled in the art. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, components and parts that play the same role are marked with the same symbols for description. In addition, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. It should be noted that the numerical range expressed as "A to B" in this specification includes A and B.

[0016] It should be noted that, in this specification, a "secondary battery" refers to an electrical storage device that can be repeatedly charged and discharged. Furthermore, in this specification, a "non-aqueous electrolyte secondary battery" refers to any battery that can be repeatedly charged and discharged by the transfer of charge carriers between the positive and negative electrodes via a non-aqueous electrolyte. Furthermore, a "lithium-ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and is charged and discharged by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0017] The present invention will be described in detail below using a flat rectangular lithium-ion secondary battery having a flat wound electrode body and a flat battery case as an example. However, the present invention is not intended to be limited to the contents described in this embodiment.

[0018] Figure 1 1 is a cross-sectional view schematically showing the internal structure of the non-aqueous electrolyte secondary battery 100 disclosed herein. Figure 1 The non-aqueous electrolyte secondary battery 100 shown is a sealed battery constructed by housing a flat wound electrode body 20 and a non-aqueous electrolyte 80 in a flat square battery case (i.e., outer container) 30. The battery case 30 is provided with a positive terminal 42 for external connection, a negative terminal 44, and a thin-walled safety valve 36 set in a manner to release the internal pressure of the battery case 30 when the internal pressure rises to or above a specified level. In addition, the battery case 30 is provided with an injection port (not shown) for injecting the non-aqueous electrolyte 80. The positive terminal 42 is electrically connected to the positive electrode collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode collector plate 44a. As the material of the battery case 30, for example, a metal material that is lightweight and has good thermal conductivity, such as aluminum, can be used. It should be noted that Figure 1 The figure does not accurately represent the amount of the non-aqueous electrolyte solution 80 .

[0019] Figure 2 1 is an exploded schematic diagram showing the structure of the wound electrode body 20 of the non-aqueous electrolyte secondary battery 100 disclosed herein. Figure 1 and Figure 2As shown, the wound electrode body 20 has a structure in which a positive electrode sheet 50 and a negative electrode sheet 60 are stacked and wound along the longitudinal direction, with two elongated separators 70 interposed therebetween. The positive electrode sheet 50 has a positive electrode active material layer 54 formed on one or both sides (here, both sides) of an elongated positive electrode current collector 52 along the longitudinal direction. The negative electrode sheet 60 has a negative electrode active material layer 64 formed on one or both sides (here, both sides) of an elongated negative electrode current collector 62 along the longitudinal direction. The positive electrode active material layer-free portion 52a (i.e., the portion where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed) and the negative electrode active material layer-free portion 62a (i.e., the portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed) are formed to protrude outward from both ends of the wound electrode body 20 in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction). The positive electrode current collector plate 42a and the negative electrode current collector plate 44a are joined to the positive electrode active material layer non-formed portion 52a and the negative electrode active material layer non-formed portion 62a, respectively.

[0020] The positive electrode 50 (positive electrode sheet 50) has a positive electrode collector 52 and a positive electrode active material layer 54 arranged on at least one surface of the positive electrode collector 52. As the positive electrode collector 52, a known positive electrode collector used in a lithium-ion secondary battery can be used, and as an example, a sheet or foil made of a metal with good conductivity (such as aluminum, nickel, titanium, stainless steel, etc.) can be cited. As the positive electrode collector 52, aluminum foil is preferred. The size of the positive electrode collector 52 is not special, as long as it is appropriately determined according to the battery design. When aluminum foil is used as the positive electrode collector 52, its thickness is not particularly limited, for example, it is 5μm to 35μm, preferably 7μm to 20μm.

[0021] The positive electrode active material layer 54 contains a positive electrode active material. As the positive electrode active material, a known positive electrode active material used in lithium-ion secondary batteries can be used. Specifically, for example, a lithium composite oxide, a lithium transition metal phosphate compound, etc. can be used as the positive electrode active material. The crystal structure of the positive electrode active material is not particularly limited and can be a layered structure, a spinel structure, an olivine structure, etc.

[0022] As the lithium composite oxide, a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element is preferred, and specific examples thereof include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides. These positive electrode active materials may be used alone or in combination of two or more.

[0023] It should be noted that in this specification, "lithium nickel cobalt manganese composite oxide" refers to a term that refers to an oxide containing one or more additional elements other than Li, Ni, Co, Mn, and O as constituent elements, in addition to the oxide. Examples of such additional elements include transition metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn, and typical metal elements. In addition, the additional elements may also be metalloid elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This also applies to the above-mentioned lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, and lithium iron nickel manganese composite oxide.

[0024] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO 4 ), lithium manganese phosphate (LiMnPO 4 ), and lithium manganese iron phosphate.

[0025] As the positive electrode active material, lithium nickel cobalt manganese composite oxide can be used particularly preferably.

[0026] The average particle size of the positive electrode active material (the cumulative 50% particle size in the volume-based particle size distribution obtained in the particle size distribution measurement based on the laser diffraction / light scattering method) is not particularly limited, and is, for example, 0.05 μm to 25 μm, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm.

[0027] The positive electrode active material layer 54 may also contain components other than the positive electrode active material, such as a conductive material and a binder. Preferred conductive materials include carbon black (e.g., acetylene black (AB)), carbon nanotubes, graphite, and other carbon materials. Binders include polyvinylidene fluoride (PVdF), for example.

[0028] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 70% by mass or greater, more preferably 80% by mass to 97% by mass, and even more preferably 85% by mass to 96% by mass. The content of the conductive material in the positive electrode active material layer 54 is not particularly limited, but is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 13% by mass. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 1% by mass to 15% by mass, and more preferably 1.5% by mass to 10% by mass.

[0029] The thickness of the positive electrode active material layer 54 is not particularly limited, and is, for example, 10 μm to 400 μm, and preferably 20 μm to 300 μm.

[0030] The positive electrode sheet 50 may include an insulating layer (not shown) at the boundary between the positive electrode active material layer non-formed portion 52a and the positive electrode active material layer 54. The insulating layer contains, for example, ceramic particles.

[0031] The negative electrode 60 has a negative electrode collector 62 and a negative electrode active material layer 64 fixed on at least one surface of the negative electrode collector 62. As the negative electrode collector 62, a known negative electrode collector used in a lithium-ion secondary battery can be used, and as an example, a sheet or foil made of a metal with good conductivity (such as copper, nickel, titanium, stainless steel, etc.) can be cited. Copper foil is preferably used as the negative electrode collector 62. The size of the negative electrode collector 62 is not special, as long as it is appropriately determined according to the battery design. When copper foil is used as the negative electrode collector 62, its thickness is not particularly limited, for example, it is 5μm to 35μm, preferably 6μm to 20μm.

[0032] The negative electrode active material layer 64 of the non-aqueous electrolyte secondary battery 100 disclosed herein was found to have sulfur (S) element introduced into the film formed on the negative electrode in the form of SOx in X-ray photoelectron spectroscopy (XPS). Moreover, it was found that when the SOx concentration was 0.3 atomic % or more, the resistance increase rate of the non-aqueous electrolyte secondary battery 100 after storage was appropriately suppressed, and the capacity retention rate was high even after storage. Although it is not intended to limit the technology disclosed herein, the reason why this effect can be obtained is speculated as follows. In the non-aqueous electrolyte secondary battery 100 after activation treatment, a portion of the non-aqueous electrolyte 80 is reduced and decomposed to form a film called SEI film (Solid Electrolyte Interface) on the surface of the negative electrode. If the SEI film is properly formed, the negative electrode is stabilized, and a non-aqueous electrolyte secondary battery 100 with good storage characteristics can be provided. On the other hand, when the SEI film is excessively formed, there is a tendency for the storage characteristics of the secondary battery to decrease (for example, the resistivity after storage increases and the capacity retention rate decreases). According to the results of research conducted by the present inventors, sulfur (S) is introduced into the film formed on the negative electrode in the form of SOx, and the SOx concentration is high (specifically, 0.3 atomic % or higher). This suppresses excessive SEI film formation (growth), enabling the formation of a suitable SEI film on the negative electrode. This SEI film has low resistance and reduces irreversible lithium loss. This results in a non-aqueous electrolyte secondary battery 100 with excellent storage characteristics.

[0033] The presence of SOx on the negative electrode can be confirmed by, for example, X-ray photoelectron spectroscopy (XPS) analysis. Specifically, the XPS spectrum measured by XPS has a peak Ps attributable to SOx at a position with a binding energy of 165 to 175 eV (for example, around 169 eV). This peak Ps means the presence of SOx. In addition, the SOx state ratio (SOx concentration) in the negative electrode active material layer can be measured by XPS analysis. Specifically, the SOx state ratio can be determined by correcting the peak area of ​​the peak Ps obtained by using a sensitivity coefficient that takes into account the ease of generation of photoelectrons. It should be noted that the SOx state ratio refers to the state ratio (concentration) of SOx on the outermost surface of the negative electrode active material layer 64 when the peak area obtained in the range of 0 to 1100 eV is expressed in atomic percentage (100 atomic %).

[0034] The SOx concentration (SOx state ratio) measured by the above method may be 0.3 atomic % or higher, 0.4 atomic % or higher, or 0.5 atomic % or higher. The upper limit of the SOx concentration in the negative electrode active material layer is not particularly limited and may be 2 atomic % or lower, 1 atomic % or lower, or 0.7 atomic % or lower.

[0035] The negative electrode active material layer 64 contains a negative electrode active material. In the non-aqueous electrolyte secondary battery 100 disclosed herein, the negative electrode active material comprises a carbon material and an amorphous carbon coating layer covering the carbon material. The type of carbon material is not particularly limited, and examples thereof include natural graphite and artificial graphite. The amorphous carbon coating layer may be composed of, for example, non-graphitizable carbon, readily graphitizable carbon, activated carbon, and the like. The negative electrode active material is preferably amorphous carbon-coated graphite formed by coating the surface of graphite with a carbon material having low crystallinity.

[0036] As described above, the negative electrode active material comprises a carbon material and an amorphous carbon coating covering the carbon material. In other words, the negative electrode active material may be a mixture or a composite of carbon materials with different crystallinity. Here, the crystallinity of the negative electrode active material may be evaluated by Raman spectroscopy. The measurement of Raman spectra may appropriately adopt a conventionally known method. For example, the Raman spectrum may be measured by laser Raman spectroscopy using an appropriate laser (such as an argon ion laser) as a light source. The negative electrode active material of the non-aqueous electrolyte secondary battery 100 disclosed herein has a Raman spectrum of 1360 cm in the Raman spectrum analysis measured by Raman spectroscopy. -1 The peak intensity D and 1580 cm -1The intensity ratio (D / G) of the peak intensity G is 0.3 to 0.5. The D / G ratio is the ratio of the intensity of the D peak reflecting the irregular structure to the intensity of the G peak reflecting the regular graphite structure, and is also called the R value. By adjusting the intensity ratio (D / G) to 0.3 to 0.5, it can be said that the negative electrode active material has appropriate crystallinity. By combining the negative electrode active material with the intensity ratio (D / G) adjusted to 0.3 to 0.5 with the non-aqueous electrolyte described later, the SOx concentration in the negative electrode active material layer 64 can be appropriately increased.

[0037] It should be noted that in this specification, the above “1580cm -1 The peak intensity at 1580 cm -1 Nearby (e.g. 1580cm -1 ~1620cm -1 In this specification, the peak intensity of the above-mentioned "1360cm -1 The peak intensity at 1360 cm -1 Nearby (e.g. 1300cm -1 ~1400cm -1 The peak intensity of the range (D band)).

[0038] The intensity ratio (D / G) of the negative electrode active material may be 0.3 or greater, 0.32 or greater, 0.34 or greater, or 0.35 or greater. Furthermore, the intensity ratio (D / G) of the negative electrode active material may be 0.5 or less, 0.48 or less, 0.45 or less, 0.42 or less, 0.4 or less, or 0.38 or less. Thus, a negative electrode active material having neither excessively high nor excessively low crystallinity can be realized.

[0039] The negative electrode active material is preferably in a granular form. While not particularly limited, the average particle size of the negative electrode active material (the cumulative 50% particle size in the volume-based particle size distribution obtained by particle size distribution measurement using a laser diffraction / light scattering method) is, for example, 0.5 μm to 50 μm, preferably 1 μm to 20 μm, and more preferably 5 μm to 10 μm.

[0040] The negative electrode active material having the above-mentioned intensity ratio (D / G) can be manufactured using a conventionally known method. For example, first, a graphite material and an amorphous carbon material (e.g., easily graphitized carbon) are prepared as raw materials. Next, the amorphous carbon material is attached to the surface of the graphite material by a gas phase method such as CVD (Chemical Vapor Deposition), or a liquid phase method, a solid phase method, or the like. Then, the graphite material to which the amorphous carbon material is attached is calcined at, for example, about 800 to 1500°C to carbonize it, thereby enabling the manufacture of a negative electrode active material (amorphous carbon-coated graphite). It should be noted that the D / G value of the negative electrode active material can be adjusted by, for example, the D / G value of the raw materials (graphite material and / or amorphous carbon material) used, the mixing ratio of the raw materials, the calcination temperature during calcination, and the like.

[0041] The negative electrode active material layer 64 may contain conventional components other than the active material, such as a binder and a thickener. Examples of binders include styrene-butadiene rubber (SBR) and polyvinylidene fluoride (PVdF). Examples of thickeners include carboxymethyl cellulose (CMC).

[0042] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or greater, more preferably 95% to 99% by mass. The content of the binder in the positive electrode active material layer 64 is preferably 0.1% to 8% by mass, more preferably 0.5% to 3% by mass. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% to 3% by mass, more preferably 0.5% to 2% by mass.

[0043] The thickness of the negative electrode active material layer 64 is not particularly limited, and is, for example, 10 μm to 400 μm, and preferably 20 μm to 300 μm.

[0044] As the separator 70 (separator sheet 70), for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) containing ceramic particles can also be provided on the surface of the separator 70. The thickness of the separator 70 is not particularly limited, and is, for example, 5 μm to 50 μm, preferably 10 μm to 30 μm.

[0045] The non-aqueous electrolyte 80 contains a non-aqueous solvent and an electrolyte salt (also called a supporting salt). The non-aqueous electrolyte 80 contains at least a sulfur-based electrolyte salt, a carbonate-based solvent, and methyl acetate (methyl acetate). By combining such a non-aqueous electrolyte with a negative electrode active material having the aforementioned D / G ratio appropriately adjusted, SOx from the sulfur-based electrolyte salt can be appropriately introduced to the surface of the negative electrode active material layer 64, thereby increasing the SOx concentration. This suppresses the increase in resistance of the non-aqueous electrolyte secondary battery 100 after storage and suppresses the decrease in capacity retention.

[0046] The sulfur-based electrolyte salt is not particularly limited as long as it is an electrolyte salt containing a sulfur atom. As the sulfur-based electrolyte salt, for example, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethane)sulfonylimide (LiTFSI) and the like can be cited. Among them, the sulfur-based electrolyte salt preferably includes LiFSI. The concentration of the sulfur-based electrolyte salt in the non-aqueous electrolyte is not particularly limited, and is preferably 0.5% to 3% by mass, and more preferably 0.5% to 1.5% by mass.

[0047] The non-aqueous electrolyte solution 80 may also contain electrolyte salts other than sulfur-based electrolyte salts. Examples of such electrolyte salts include LiPF6 and LiBF4. The concentration of the electrolyte salts other than sulfur-based electrolyte salts in the non-aqueous electrolyte solution is not particularly limited, but is preferably 0.7 mol / L to 1.3 mol / L.

[0048] The non-aqueous electrolyte secondary battery 100 disclosed herein includes a carbonate-based solvent and methyl acetate as a non-aqueous solvent. Examples of carbonate-based solvents include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyldifluoromethyl carbonate (F-DMC), and dimethyl trifluorocarbonate (TFDMC). Such carbonate-based solvents can be used alone or in combination of two or more. Among them, as a carbonate-based solvent, it is preferred that at least ethylene carbonate be included.

[0049] From the perspective of appropriately increasing the SOx concentration on the surface of the negative electrode active material layer, the nonaqueous solvent preferably contains at least 10 vol% or more of methyl acetate, based on the total volume of 100 vol%. The methyl acetate content is, for example, preferably 20 vol% or more, more preferably 30 vol% or more. The upper limit of the methyl acetate content is not particularly limited, but is, for example, preferably 80 vol% or less, more preferably 70 vol% or less. The methyl acetate content (vol%) can be determined, for example, by NMR analysis.

[0050] Although not particularly limited, the ratio of the carbonate solvent to methyl acetate in the non-aqueous solvent is preferably 90:10 to 20:80, and more preferably 90:10 to 30:70. This allows the aforementioned effects to be more stably exhibited, and the storage characteristics of the non-aqueous electrolyte secondary battery 100 can be appropriately improved.

[0051] The non-aqueous electrolyte 80 may also contain components other than the non-aqueous solvent and the electrolyte salt (hereinafter referred to as "optional components"). Preferred examples of such optional components include film-forming agents such as vinylene carbonate and oxalic acid complexes; thickeners; and various additives such as gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB).

[0052] The above description uses a rectangular non-aqueous electrolyte secondary battery 100 having a flat wound electrode body 20 as an example. However, a lithium-ion secondary battery can also be configured as a non-aqueous electrolyte secondary battery having a stacked electrode body (i.e., an electrode body composed of multiple positive electrodes and multiple negative electrodes alternately stacked). Furthermore, a lithium-ion secondary battery can also be configured as a cylindrical non-aqueous electrolyte secondary battery, a laminated shell non-aqueous electrolyte secondary battery, or the like.

[0053] The non-aqueous electrolyte secondary battery 100 can be used in a variety of applications, but is particularly suitable for use as a power source (driving power source) for motors installed in mobile vehicles, such as passenger cars and trucks, due to its ability to balance the reduction in resistance increase and capacity retention after storage. The type of vehicle is not particularly limited, and examples include plug-in hybrid electric vehicles (PHEVs), hybrid electric vehicles (HEVs), and battery electric vehicles (BEVs). The non-aqueous electrolyte secondary battery 100 can also be used in the form of a battery pack, consisting of multiple batteries connected in series and / or in parallel.

[0054] Hereinafter, examples of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these examples.

[0055] (Example 1)

[0056] Graphite coated with amorphous carbon was prepared as the negative electrode active material. Specifically, commercially available graphite and coal tar pitch, a raw material for the amorphous carbon, were first prepared. Next, the coal tar pitch was deposited onto the graphite surface using CVD. The graphite coated with the coal tar pitch was then calcined at 800-1500°C in a non-oxidizing atmosphere to produce graphite coated with amorphous carbon. This was used as the negative electrode active material in Example 1.

[0057] Next, styrene-butadiene rubber (SBR) as a binder and carboxymethyl cellulose (CMC) as a thickener were prepared. The negative electrode active material prepared in Example 1 was mixed with SBR and CMC in a mass ratio of negative electrode active material: SBR: CMC = 98:1:1, along with ion-exchanged water to prepare a negative electrode slurry. This slurry was applied to both sides of a long copper foil strip, dried, and then pressed to produce a negative electrode sheet.

[0058] Next, prepare LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM), acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed with N-methylpyrrolidone (NMP) at a mass ratio of NCM:AB:PVdF = 92:5:3 to prepare a slurry for forming the positive electrode active material layer. This slurry was applied to both sides of a long aluminum foil in a strip shape, dried, and then pressed to form a positive electrode sheet.

[0059] A separator was prepared by placing HRL on a porous polyolefin sheet of a three-layer structure of PP / PE / PP. The positive electrode sheet, negative electrode sheet, and two separators prepared above were stacked and wound to produce a wound electrode body.

[0060] Next, prepare a non-aqueous electrolyte. As a carbonate-based solvent, prepare ethylene carbonate and dimethyl carbonate. Prepare a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and methyl acetate (MA) in a volume ratio of 30:70-X:X. It should be noted that the value of X (volume ratio, also volume %) is the value shown in Table 1. In this mixed solvent, lithium bis(fluorosulfonyl)imide (LiFSI) is dissolved at a concentration of 0.5% by mass, and LiPF6 as an electrolyte salt is dissolved at a concentration of 1.0 mol / L. Thus, a non-aqueous electrolyte is prepared.

[0061] The terminals were attached to the electrode assembly prepared above, and the assembly was placed in a battery case together with the prepared nonaqueous electrolyte, and hermetically sealed. An activation treatment was then performed to obtain the lithium ion secondary battery for evaluation of Example 1.

[0062] (Examples 2 and 3)

[0063] In Examples 2 and 3, the content (vol %) of methyl acetate (MA) was changed as shown in Table 1. Otherwise, the same procedure as in Example 1 was carried out to produce lithium ion secondary batteries for evaluation of Examples 2 and 3.

[0064] (Example 4)

[0065] In Example 4, the calcination temperature was changed to vary the crystallinity of the outermost surface of the negative electrode active material. In addition, the content (vol%) of methyl acetate (MA) was changed as shown in Table 1. A lithium ion secondary battery for evaluation of Example 4 was prepared in the same manner as in Example 1 except for this.

[0066] (Comparative Example 1)

[0067] In Comparative Example 1, the content (vol %) of methyl acetate (MA) was changed as shown in Table 1. Otherwise, the same procedures as in Example 1 were carried out to produce a lithium ion secondary battery for evaluation of Comparative Example 1.

[0068] [Comparative Examples 2 to 4]

[0069] In Comparative Examples 2 to 4, the calcination temperature was varied to vary the crystallinity of the outermost surface of the negative electrode active material. Furthermore, the methyl acetate (MA) content (vol%) was varied as shown in Table 1. Otherwise, the same procedures as in Example 1 were followed to produce lithium ion secondary batteries for evaluation of Comparative Examples 2 to 4.

[0070] [Comparative Examples 5 to 7]

[0071] In Comparative Examples 5 and 7, the calcination temperature was changed to make the crystallinity of the outermost surface of the negative electrode active material different. In addition, in Comparative Examples 5 to 7, methyl propionate (MP) was used instead of methyl acetate. Then, the content (vol%) of the methyl propionate was changed as shown in Table 1. That is, in Comparative Examples 5 to 7, a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and methyl propionate (MP) was prepared in a volume ratio of 30:70-X:X. Except for this, the same procedure as in Example 1 was carried out to produce lithium ion secondary batteries for evaluation of Comparative Examples 5 to 7.

[0072] <Determination of initial capacity>

[0073] Each activated evaluation lithium-ion secondary battery was charged to 4.10 V at a current of 0.2 C, then charged to a full charge state using a constant current-constant voltage method (1 / 50 C). The battery was then discharged to 3.00 V using a current of 0.2 C, followed by a constant voltage method (1 / 50 C). The discharge capacity at this point was measured and used as the initial capacity of each evaluation lithium-ion secondary battery.

[0074] <Evaluation of resistance increase rate>

[0075] With the initial capacity set to SOC 100%, each evaluation lithium-ion secondary battery was charged in a -10°C thermostat at a current of 1C until it reached SOC 50%. Next, the battery was charged for 10 seconds in a -10°C thermostat at currents of 1C, 3C, 5C, and 10C. The battery voltage after charging at each current value was measured. The IV characteristics during charging were plotted against the battery voltage at each current value, and the IV resistance (Ω) during discharge was calculated from the slope of the resulting straight line. This value was used as the initial resistance value of each evaluation lithium-ion secondary battery.

[0076] Next, the above-mentioned initial capacity is set to SOC100%, and each evaluation lithium ion secondary battery is charged at a current value of 15C in a thermostat at -10°C until it reaches SOC50%. Each evaluation lithium ion secondary battery is placed in a thermostat set at 60°C and stored for 150 days. Then, in a thermostat at -10°C, charging is performed for 10 seconds at current values ​​of 1C, 3C, 5C and 10C, and the battery voltage after charging at each current value is measured. Plot each current value and each battery voltage to determine the IV characteristics during charging, and determine the IV resistance (Ω) during discharge based on the slope of the obtained straight line. This value is used as the resistance value after storage of each evaluation lithium ion secondary battery. The resistance increase rate (%) is calculated according to the formula: (IV resistance value after storage / initial IV resistance value)×100. The ratio of the resistance increase rate of the other lithium ion secondary batteries for evaluation to the lithium ion secondary battery for evaluation of Comparative Example 6 was determined, with the resistance increase rate of the lithium ion secondary battery for evaluation of Comparative Example 6 being 100. The results are shown in Table 1.

[0077] <Evaluation of Capacity Retention Rate>

[0078] After the above storage, each evaluation lithium ion secondary battery was charged to 4.10V at a current value of 0.2C, and then charged at a constant voltage to a constant current-constant voltage charge with a current value of 1 / 50C to form a fully charged state. After the constant current discharge was carried out at a current value of 0.2C to 3.00V, the constant voltage discharge was carried out to a constant current-constant voltage discharge with a current value of 1 / 50C. The discharge capacity at this time was measured and used as the discharge capacity after storage. Using the initial capacity and discharge capacity measured above, the capacity retention rate (%) was calculated according to the formula: (discharge capacity after storage / initial capacity) × 100. The ratio of the initial resistance of the other evaluation lithium ion secondary batteries to the evaluation lithium ion secondary battery of Comparative Example 6 was calculated when the capacity retention rate of the evaluation lithium ion secondary battery of Comparative Example 6 was set to 100. The results are shown in Table 1.

[0079] <Calculation of the D / G ratio>

[0080] After the storage test, the evaluation lithium-ion secondary batteries of each example were disassembled and the negative electrode active material was analyzed. The negative electrode active material of each example was analyzed using a Raman spectrometer (microscopic Raman spectrometer manufactured by Renishaw, inVia Reflex 785S, excitation wavelength 532nm, Ar laser) to obtain a Raman spectrum. The Raman spectrum was measured at 1580cm -1 The peak intensities G and 1360 cm -1 The peak intensity D was obtained, and the ratio of the peak intensity D to the peak intensity G (D / G ratio) was determined. The calculated values ​​are shown in Table 1.

[0081] <XPS measurement of negative electrode active material layer>

[0082] After the storage test, the lithium-ion secondary batteries for evaluation of each example were disassembled and the negative electrode active material layer was analyzed using XPS. Specifically, an XPS apparatus ("PHI 5000 VersaProbe 2" manufactured by ULVAC-PHI) was used with an X-ray source of AlKα radiation (monochromatic light) and an irradiation range of The negative electrode active material layers were measured under the conditions of current and voltage: 25kW and 15kV. Based on the obtained XPS spectrum, a curve fitting was performed with respect to the SOx peak Ps appearing at a position with a binding energy of approximately 169eV to determine the peak area. It should be noted that the peak offset correction was performed after correcting the C1s peak to 284.80eV. From this, the SOx concentration (atomic %) was calculated. The results are shown in Table 1.

[0083] [Table 1]

[0084]

[0085] As shown in Table 1, Examples 1 to 4, in which the D / G ratio of the negative electrode active material was 0.3 to 0.5, the non-aqueous electrolyte contained a sulfur-based electrolyte salt, a carbonate-based solvent, and methyl acetate, and the SOx concentration based on XPS was 0.3 atomic % or greater, exhibited a low resistance increase rate and a high capacity retention rate. These results demonstrate that the non-aqueous electrolyte secondary battery disclosed herein achieves a non-aqueous electrolyte secondary battery that appropriately suppresses resistance increases even after storage and maintains a high capacity retention rate.

[0086] The above detailed description of the technology disclosed herein is for illustrative purposes only and does not limit the scope of the claims. The technology described in the claims includes various modifications and variations of the specific examples described above.

[0087] As described above, specific aspects of the technology disclosed herein include those described in the following items.

[0088] Item 1: A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the negative electrode comprises a negative electrode active material layer containing a negative electrode active material, wherein the negative electrode active material comprises a carbon material and an amorphous carbon coating covering the carbon material, and wherein the negative electrode active material has a Raman spectrum at 1360 cm-1 as measured by Raman spectroscopy. -1 The peak intensity D and 1580 cm -1 The intensity ratio (D / G) of the peak intensity G is 0.3 to 0.5, the non-aqueous electrolyte contains at least a sulfur-based electrolyte salt and a non-aqueous solvent, the non-aqueous solvent contains a carbonate-based solvent and methyl acetate, wherein the SOx concentration of the negative electrode active material layer is greater than 0.3 atomic %, and the SOx concentration is calculated based on an XPS spectrum measured by X-ray photoelectron spectroscopy.

[0089] Item 2: The non-aqueous electrolyte secondary battery according to Item 1, wherein the content of methyl acetate in the non-aqueous solvent of the non-aqueous electrolyte is 10 vol% to 70 vol% when the entire non-aqueous solvent is taken as 100 vol%.

[0090] Item 3: The non-aqueous electrolyte secondary battery according to Item 1 or 2, wherein the carbonate-based solvent contains at least ethylene carbonate.

[0091] Item 4: The non-aqueous electrolyte secondary battery according to any one of Items 1 to 3, wherein the sulfur-based electrolyte salt comprises lithium bis(fluorosulfonyl)imide.

[0092] Explanation of symbols

[0093] 20 wound electrode bodies

[0094] 30 battery case (outer container)

[0095] 36 safety valve

[0096] 42 positive terminal

[0097] 42a positive electrode collector plate

[0098] 44 negative terminal

[0099] 44a negative electrode collector plate

[0100] 50 positive electrode (positive electrode sheet)

[0101] 52 positive electrode collector

[0102] 52a Positive electrode active material layer non-formed portion

[0103] 54 positive electrode active material layer

[0104] 60 negative electrode (negative plate)

[0105] 62 negative electrode collector

[0106] 62a Negative electrode active material layer non-formed portion

[0107] 64 Negative electrode active material layer

[0108] 70 Isolation piece (spacer)

[0109] 80 non-aqueous electrolyte

[0110] 100 non-aqueous electrolyte secondary battery

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The negative electrode comprises a negative electrode active material layer containing a negative electrode active material. The negative electrode active material comprises a carbon material and an amorphous carbon coating layer covering the carbon material. The negative electrode active material has a Raman spectrum at 1360 cm-1 in Raman spectroscopy analysis measured by Raman spectroscopy. -1 The peak intensity D and 1580cm -1 The intensity ratio of the peak intensity G, i.e. D / G, is 0.3 to 0.

5. The non-aqueous electrolyte solution contains at least a sulfur-based electrolyte salt and a non-aqueous solvent. The non-aqueous solvent comprises a carbonate solvent and methyl acetate, in, The negative electrode active material layer has a SOx concentration of 0.3 atomic % or more, and the SOx concentration is calculated based on an XPS spectrum measured by X-ray photoelectron spectroscopy.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein: In the non-aqueous solvent of the non-aqueous electrolyte, the content of methyl acetate is 10 vol% to 70 vol% when the entire non-aqueous solvent is taken as 100 vol%.

3. The non-aqueous electrolyte secondary battery according to claim 1, wherein The carbonate-based solvent contains at least ethylene carbonate.

4. The non-aqueous electrolyte secondary battery according to claim 1, wherein The sulfur-based electrolyte salt includes lithium bis(fluorosulfonyl)imide.

Citation Information

Patent Citations

  • Electrolyte for lithium secondary batteries, and lithium secondary battery including the same

    JP2017103240A

  • Lithium metal secondary battery

    JP2019160730A

  • Non-aqueous electrolyte and non-aqueous electrolyte secondary battery containing said non-aqueous electrolyte

    JP2022129682A